Do Upper and Lower Camptocormias Affect Gait and Postural Control in Patients with Parkinson’s Disease? An Observational Cross-Sectional Study - Christian Geroin; Marialuisa Gandolfi; Isacco Maddalena; Nicola Smania; Michele Tinazzi (Parkinson's Disease)
Gait impairments and camptocormia (CC) are common and debilitating in patients with Parkinson’s disease (PD). Two types of CC affect patients with PD, but no studies investigated their relative contribution in worsening gait and postural control. Therefore, we investigated spatiotemporal gait parameters, gait variability, and asymmetry and postural control in PD patients (Hoehn & Yahr ≤4) with upper CC and lower CC and patients without CC. This observational cross-sectional study involving patients with PD and upper CC (n=16) and lower CC (n=14) and without CC (n=16). The primary outcome measure was gait speed assessed by the GAITRite System. The secondary outcome measures were other spatiotemporal parameters, gait variability, and asymmetry. Postural control and balance were assessed with posturography and the Mini-BESTest. Patients with lower CC showed a higher H&Y stage (p=0.003), a worse PDQ8 (p=0.042), and a lower Mini-BESTest score (p=0.006) than patients with PD without CC. Patients with lower CC showed a reduced gait speed (p=0.012), stride length, and velocity than patients with PD without CC. Upper CC patients showed a higher stride length than lower CC ones (p=0.007). In the eyes open and closed condition, patients with lower CC showed a higher (worse) velocity of CoP displacement in mediolateral direction and length of CoP than patients with PD without CC. No significant between-group differences were measured in gait variability and asymmetry. In conclusion, lower CC was associated with more severe gait and postural control impairment than patients with upper CC and without CC. Categorizing CC based on the bending fulcrum is compulsory to identify patients with the worst performance and to implement specific rehabilitation programs.